M-PESA AND ITS PERCEIVED EFFECT ON PERFORMANCE OF MANUFACTURING FIRMS: A CASE STUDY OF THIKA TOWN IN KENYA - Maina Kiganane, Lucy (Advances in Social Sciences Research Journal, 2015)
During the last decade great expansion of information and communication technologies has taken place and indeed set the stage for a new era of entrepreneurial opportunities and challenges worldwide. The ever increasing development of technology has led businesses to continually assess whether new technology is worth investing in and could possibly enhance their business activities. Mobile Technology has indisputably been one of the most considerable contributors of good performance in business. Mobile technology which is the advent of entrepreneurial innovation has gained attention worldwide and is increasingly used to support performance in various manufacturing firms. Firms are applying this entrepreneurial innovation to achieve various business benefits including efficiency and effectiveness through improved productivity, cost savings, and reach ability communication and customer satisfaction. In March 2007, Safaricom mobile operator launched M-Pesa the mobile money transfer system which has become a popular mobile payment system with both the banked and the unbanked Kenyan population and has revolutionized the mode of conducting business in Kenya. However, very little had been done to assess the perceived effect of MPESA service on performance of manufacturing firms. This called for more research and the fact that more work on money transfer had been done outside Kenya constituted the need to study the Kenyan situation to see which side of the debate Kenyan results would fall. This study therefore sought to establish the perceived effect of MPESA mobile service on performance of manufacturing firms in Thika town in Kenya. A two-stage sampling technique was employed. In the first stage firms were divided into three groups (Small, Medium and Large) according to the number of employees. In the second stage simple random sampling technique was applied where each manufacturing firm from each 2 category was given a serial number in its respective category and the numbers picked at random. A total of 120 questionnaires were self-administered yielding 100% response rate. The data was subjected to detailed exploratory analysis through descriptive and inferential analysis. Reliability and internal consistency of the measurement scale was tested using Cronbach‟s alpha. Analysis of Variance (ANOVA) was engaged to calculate the statistical significant differences between means. Post Hoc analysis was conducted using the Scheffe test to check the statistical significant differences between independent variables constituting the firm characteristics. Multiple regression analysis was engaged to analyze, establish relationship between variables and test the hypothesis. Findings revealed M-Pesa was frequently used and was perceived to have great positive effect on the performance of manufacturing firms. The location of the firm from the town Centre moderated the effect of M-PESA 2kms away from CBD. Results of the study revealed that M-PESA mobile phone service was perceived to have significantly increased sales volume, profit, worker productivity, and customer satisfaction ratings. These Results therefore confirm that it is worth for firms to adopt and adapt to the new techno status quo resulting from entrepreneurial innovations in order to not only survive in the market but also attain a competitive edge.